Analysis of Accident-Prone Areas in North Jakarta - Widodo Budi Dermawan; Muhamad Yuan Kelvin Fuadi; Muhammad Isradi; Amar Mufhidin (Neutron, 2021)
Transportation is an important part of human life, which has the benefit of facilitating the movement of people and the transportation of goods. This study aims to determine and analyze the locations where accidents often occur along the Cakung - Cilincing road, North Jakarta and determine what factors cause accidents along this road. The research on the analysis of accident-prone areas used the observation method with the quantity data provided by the North Jakarta Police Traffic Unit through IRSMS data, and the survey method was carried out on roads with the recording of passing vehicles, followed by calculations according to MKJI 1997. The results of the study were the location coordinates of the locations that had the highest value Accident-prone, namely segment 3 at the coordinate point -6.140891 to -6.13712 with an AEK value of 80 which causes 6 deaths, 0 serious injuries, 1 minor injury, 5 objects losses, and Rp.13,200,000 material loss. The number of accidents at the coordinate point was 5 incidents. The value of material losses from accidents on Jalan Cakung Cilincing reached Rp. 92,900,000 for the last 4 years from 2016 - 2019. And research on road segment performance obtained LOS A with DS 0.06 in the morning, 0.06 in the afternoon, and 0, 07 in the afternoon.